Perlindungan Hukum Hak Asasi Pelaku Terorisme sebagai Bentuk Penerapan Hukum yang Berkepastian dan Berkeadilan - Fikry Latukau (Journal of Judicial Review, 2020)
In law enforcement certainly do not forget about some of the objectives of the law itself namely Legal Certainty, justice and expediency. Of course, in its implementation, one of the three should not be ruled out, meaning that the three objectives of the law must be considered. One form of State protection for its citizens is by using statutory regulations to limit behavior citizens in doing or not doing something, in this article will be studied in depth about the rights of perpetrators of terrorism in law enforcement in Indonesia associated with several conventions and declarations. this research is normative or library research.